An Electrochemical Sensor for the Determination of Cu(Ii) Using a Modified Electrode with Ferrocenyl Crown Ether Compound by Square Wave Anodic Stripping Voltammetry - Segura-Segura, R; Segura-Segura, R; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Gomez-San Martin, A; Gomez-San Martin, A; Agurto-Doren, N; Agurto-Doren, N; Pizarro-Reyes, J; Pizarro-Reyes, J; Flores-Vergara, E; Flores-Vergara, E; et al. (Elsevier B.V., 2017)
An electrochemical sensor based on a glassy carbon electrode modified with ferrocenyl imine [(η5-C5H4CH=N-4′-benzo-15-crown-5)Fe(η5-C5H5)] (FcIB15C5) has been developed for the determination of Cu(II) using square wave anodic stripping voltammetry (SWASV). The metalloligand was synthesized from ferrocene-carboxaldehyde and 4′-aminobenzo-15-crown-5. The metalloligand FcIB15C5 was characterized by FT-IR, 1H - 13C NMR spectroscopies and mass spectrometry and was obtained as a single isolated isomer (E-configuration). The optimum conditions for the prepared electrode were as follows: Britton–Robinson buffer with pH = 6.0, FcIB15C5 concentration = 0.3 mM, accumulation potential (Eacc) = −0.8 V and accumulation time (tacc) = 90 s. A linear range was observed from 10 to 70 μg L−1 with a limit of detection (LOD) of 0.11 μg L−1. The proposed procedure was validated with TMDA-64.2 and CRM-TMDW certified reference materials, and it showed good accuracy and precision. The methodology was applied to a mining effluent and urine samples with satisfactory results. © 2017 Elsevier B.V.
Keywords: Macrocylic fragment; Ferrocenyl imine; Electrochemical sensor; Square wave anodic stripping voltammetry; Copper